Globalization and Ukraine: Vector’s Aspect of the Further Economic Development - Duka, Anastasiia; Tkachenko, Iulіia (My University, 2013)
In the last years the humanity assists to the fundamental changes in economy no matter the level from which is regarded. These changes are so fast and intensive that many times the humanity is confronting also with adaptation difficulties and also with the collapses of some value systems which have proved themselves incompatible with new realities to the world level. So, we’ve became the witnesses of a world in which the commercial bounds and the capital fluxes between countries have grown so much that the globalization of the world economy is a reality. The globalization is a term used to describe a multi -causative process which has as result the fact that the events which takes place in some part of the globe have more and more wide repercussive on the societies an d on the problems from other parts of the globe. It influences all aspects of the life, including economic development. Therefore, it’s very important to investigate the influence of this factor in any economic research.
Keywords: кафедра економіки праці та менеджменту; EU; globalization; ratings; Post-Soviet countries; Ukraine; ЄС; глобалізація; рейтинги; пострадянські країни; Україна; ЕС; глобализация; постсоветские страны; Украина